Iowa Birdline update, June 21, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for June 21, 1993. Highlights of the update include sightings of Upland Sandpipers and Swainson's Hawks. Also included are handwritten notes for the next week's update with sightings of Northern Mockingbirds nesting in Madison County and two Peregrine Falcons tending to three young. Epson - sheet feed/flatbed